(untitled) (Journal of the College of Basic Education, 2023)
On July 12, 2006, Hezbollah fighters carried out a qualitative operation, and were able to kill and injure a number of "Israeli" soldiers and capture two others. It was called the “Truthful Promise” in reference to the promise of Sayyed Hassan Nasrallah, Secretary General of Hezbollah, to free the rest of the prisoners, and he announced a formula to release the two captured soldiers in exchange for the liberation of the remaining Lebanese and Arab detainees in “Israel” prisons. The Iraqi press followed the developments of the aggression on a daily basis, especially the position of the Supreme Religious Authority in Najaf, and the Presidency of the Republic, regarding the Israeli massacres, and UN Resolution 1701, and the war constituted a historical turning point that made the Lebanese resistance present a model for a new victory in the history of the Arab confrontation with "Israel". Hizb allah. Security Council. Qana. Southern suburb. Resolution 1701